Exploration of amination reactions on highly extendable active sites of Pd(II)-3-allylsalicylaldiminophenol (ASIP) complex over thiofunctionalized SBA-15 - Lazar, Anish; Vinod, C. P.; Singh, A. P. (Microporous and Mesoporous Materials, 2017)
An effective and impressive heterogeneous catalyst, Pd(II)-3-allylsalicylaldiminophenol-SBA-15, dubbed as Pd(II)ASIP@SBA-15, for amination reactions of aryl halides to synthesize secondary amines (2), has been synthesized and characterized. Pd(II)ASIP@SBA-15 has been synthesized by the covalent anchoring of 3-allylsalicylaldehyde over thiofunctionalized SBA-15, then further reaction with 2-aminophenol, followed by metallation process by using Pd(11)(OAc)(2). A specifically designed cheap and easily available organic ligand, 3-allylsalicylaldiminophenol (ASIP), was synthesized from 3-allylsalicylaldehyde and 2-aminophenol. Using this, the synthesis of Pd(II)ASIP@SBA-15 was carried out whereby the ligand providing an active co-ordination or chelating sites for palladium metal. This strategy helped in exposing the Pd(11)ASIP active sites from surface to channels of SBA-15 support during the reactions. The synthesized catalyst were characterized by CHN analysis, PXRD, Nitrogen sorption analyses, TG & DTA, FTIR, C-13 and Si-29 CPMASS NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. Pd(II)ASIP@SBA-15 catalyst was screened in heterogeneous amination reactions of aryl halides to produce N-aryl derivatives or secondary amines with high catalytic activity as revealed by turn over frequency (TOF) calculations. To explore the heterogeneous nature of catalysts, amination reactions were carried with neat Pd(II)ASIP complex and Pd(11)(OAc)(2) catalysts. The catalyst was recycled several times without much loss of activity and Sheldon hot filtration test has been performed. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Amination Reactions; heterogeneous catalysis; Reusable; Supported catalysis

Nickel-catalyzed N-vinylation of heteroaromatic amines via C-H bond activation - Landge, Vinod G.; Rana, Jagannath; Subaramanian, Murugan; Balaraman, Ekambaram (Organic & Biomolecular Chemistry, 2017)
Here, we report a ligand- and reductant-free nickel-catalyzed N-vinylation of heteroaromatic amines using biorenewable p-cymene as a solvent. This unprecedented cross-coupling strategy has high functional group tolerance (halides, alkoxy, cyano, chiral motif, etc.) and proceeded via C-H bond activation.
Keywords: Alkylation; Amination Reactions; Anilines; Aryl Chlorides; halides; Monoarylation; O Bonds; Precatalyst; Pyrimidines; Removeble Directing Group